Analysis of the Contribution of Energy, Industry, Agriculture and Food Production to Improving the Quality of Life of Citizens in Turkic States with Efficiency and Super Efficiency Analysis Methods - Nurgabylov, Murat; Nakhipbekova, Symbat; Tazhibayeva, Raikhan; Kaltayeva, Saule; Taizhanov, Lesbek; Seitova, Vilena; Maulenkulova, Gulbana Erzhigitovna (International Journal of Energy Economics and Policy, 2024)
One of the main goals of countries is to increase the welfare and quality of life of their citizens by using their existing wealth and production. This study aims to analyze the contribution of energy, industry, agriculture, and food production towards improving the quality of life for citizens in the Turkic States. Specifically, the study will use the efficiency and super efficiency analysis methods, known as data envelopment analysis, to analyze the years between 2017 and 2022. According to the findings, Turkiс States showed successful management in terms of GDP and health quality in 2019 and 2020. In 2021, only Kazakhstan and Turkmenistan remained below the effective limit. The efficiency analysis model for input showed that the efficiency in the energy production input variable for Kazakhstan is very low (83.9% idle capacity). The findings revealed a point of criticism since efficiency analysis assigns higher efficiency score values to countries that produce output with less input. Thus, testing the findings obtained by comparing efficiency analysis with different input-output models and analysis methods is considered an important methodological approach.